2021
DOI: 10.1101/2021.10.25.21265500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Third doses of COVID-19 vaccines reduce infection and transmission of SARS-CoV-2 and could prevent future surges in some populations: a modeling study

Abstract: Background Vaccines have greatly reduced the impact of COVID-19 globally. Unfortunately, evidence indicates that immunity wanes following vaccination, especially with the Delta variant (B.1.617.2). Protection against severe disease and death remain high, but protection against milder disease and infection have dropped significantly. A third booster dose of two-dose vaccines has been approved in several countries to individuals at higher risk of severe disease to protect those individuals, but the benefit to bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 44 publications
(28 reference statements)
0
29
0
1
Order By: Relevance
“…Third dose boosting campaigns have therefore been initiated in many countries, with recent observational studies demonstrating a rapid increase in serum neutralizing antibody (NAb) titer and breadth against highly transmissible VOC concomitant with a decrease in infection rate and associated disease 17–26 . Modeling studies have also suggested that booster vaccination could reduce community transmission 27 . While these data are encouraging, the impact of booster vaccination after waning immunity has not been determined in a rigorously controlled experimental setting.…”
Section: Main Textmentioning
confidence: 99%
“…Third dose boosting campaigns have therefore been initiated in many countries, with recent observational studies demonstrating a rapid increase in serum neutralizing antibody (NAb) titer and breadth against highly transmissible VOC concomitant with a decrease in infection rate and associated disease 17–26 . Modeling studies have also suggested that booster vaccination could reduce community transmission 27 . While these data are encouraging, the impact of booster vaccination after waning immunity has not been determined in a rigorously controlled experimental setting.…”
Section: Main Textmentioning
confidence: 99%
“…Furthermore, because precise estimates of vary by context, variant, and over time, we consider a range of values from 4 to 6. In our baseline modeling scenario, vaccines were assumed to reduce susceptibility to infection by VE S = 65%, the likelihood of transmission to others by VE I = 35%, and the likelihood of disease progression to hospitalization conditioned on infection by VE P = 86%, values which land within plausible literature estimates for the effectiveness of two doses of mRNA vaccine against the delta variant in the absence of dramatic waning and without boosting [14, 18, 21, 22]. Though less often studied in the literature, we assumed that prior SARS-CoV-2 infection would lead to 63% and 13% decreases in risk of infection and transmission based on a statistical model relating immunity to neutralization [18], and that hybrid immunity would be superior to either vaccination or prior SARS-CoV-2 infection alone.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are driven by reductions in susceptibility, disease severity, and infectiousness arising from vaccination, prior SARS-CoV-2 infection, or both. However, quantitative estimates of those reductions vary depending on which vaccine was administered [17], time since vaccination or SARS-CoV-2 infection [1517], whether an additional “booster” dose was given [18], and the variant circulating at the time of the study [29, 30]. We therefore sought to determine how our findings might change under different sets of assumptions about vaccine effectiveness by comparing our baseline scenario (VE S = 0.65, VE I = 0.35, VE P = 0.86) with a waning/low immunity scenario (VE S = 0.5, VE I = 0.1, VE P = 0.80) and a boosted/high immunity scenario (VE S = 0.8, VE I = 0.6, VE P = 0.90), as well as a scenario reflecting plausible VE values based on early observations for the omicron variant (VE S = 0.35, VE I = 0.05, VE P = 0.77; [22, 31]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The question of whether booster doses will improve the impact on transmission should be addressed as a top priority. 7 Research efforts should be directed towards enhancing existing vaccines or developing new vaccines that also protect against asymptomatic infections and onward transmission. Until we have such vaccines, public health and social measures will still need to be tailored towards mitigating community and household transmission in order to keep the pandemic at bay.…”
mentioning
confidence: 99%